Rozii Galievna Mukminova and Her Contribution to The Development of Historical Science - Tangirova Nigora Abdugani kizi (Scientific Trends, 2024)
This article reflects on the efforts of the great historian R. G. Mukminova on the path of science and her contribution to the development of historical science.
Keywords: Uzbekistan, craftsmen, academy, science, history, Samarkand, Waqf-noma.